Mother-tongue interference in the production of the English /i:/ and /I/ vowel sounds among Chinese ESL speakers - Chang, Siew Har (University ofSouthern Queensland, 1997)
The objectives of this research are to determine the extent Chinese ESL Speakers can differentiate between the English /i: / and /1/ vowel sounds, the extent of the influence of the language of instruction and mother-tongue on the production of these sounds. The respondents of this survey were categorised into two groups: the experimental and control groups. Respondents from the experimental group consisted of 25 Chinese undergraduates from Universiti Malaysia Sarawak (UNIMAS). They were further divided into two groups according to the language of instruction: Malay medium and Chinese medium. Respondents from the control group consisted of a native speaker and three undergraduates whose L1 is English. Data were collected through the distribution of questionnaires and the recording of a short text. This research found that Chinese undergraduates faced difficulty producing the /i: / sound as compared to the /1/ sound. The findings also indicated that language/medium of instruction bears no significance on the pronunciation of these sounds and finally, due to absence of the /1/ sound in the Chinese language, Chinese ESL speakers do not differentiate between the English /i: / and /I/ sounds.